Gut microbiota’s role in the enhancement of type 2 diabetes treatment by a traditional Chinese herbal formula compared to metformin - Chengdong Xia; Liya Yue; Yinyu Wang; Cuidan Li; Guannan Ma; Yingjiao Ju; Peihan Wang; Jie Wang; Xiaoyuan Jiang; Xiaotong Wang; Fei Chen (Microbiology Spectrum)
ABSTRACT Type 2 diabetes mellitus (T2DM) is a rapidly increasing metabolic disorder that poses a significant threat to global public health. Recent evidence suggests that targeting the gut microbiota through dietary and pharmaceutical interventions can effectively manage T2DM. In this study, we developed a novel Chinese herbal formula, CCM, specifically for T2DM, composed of Coptis rhizoma, Cinnamomi cortex, and Mume fructus. To evaluate CCM’s efficacy and explore its underlying mechanisms, particularly the role of the gut microbiota, diabetic C57/db/db mice were administered different doses of CCM (low, medium, high) for 4 weeks, with normal C57 mice as healthy controls and metformin as a positive control. Comprehensive clinical indicators of T2DM were measured before and after treatment. High-throughput sequencing was used to assess changes in gut microbiome composition and function. Our results showed that CCM treatment, especially at medium and high doses, resulted in more significant improvements in blood glucose, lipid profiles, and body weight compared to metformin. The CCM-treated group also exhibited more significant changes in the microbial community structure compared to the metformin group, notably enriching three beneficial microbes (>40%): Bacteroidetes spp., Akkermansia spp., and Parabacteroides spp., which correlated with improved diabetic parameters. Further analysis identified that all four microbial metabolic pathways linked to lowering blood glucose were exclusively enriched in the CCM-treated group. Of the 10 pathways related to improved blood lipid levels, five were unique to CCM. These unique pathways enriched by CCM may explain its superior therapeutic effects, indicating its distinct mechanisms in modulating gut microbiota.IMPORTANCEOur study demonstrates that CCM outperforms metformin in managing key clinical indicators in type 2 diabetes mellitus (T2DM) model mice and induces more significant alterations in gut microbiota composition and function. Notably, the uniquely enriched beneficial microbes and microbial metabolic pathways in the CCM samples may explain its enhanced therapeutic effects compared to metformin. Consequently, these findings suggest that CCM offers a promising therapeutic strategy for T2DM, and further provide valuable insights into potential probiotic candidates (such as Bacteroidetes spp., Akkermansia spp., and Parabacteroides spp.) and newly identified functional pathways (such as chondroitin sulfate degradation, geraniol degradation, biotin biosynthesis, colonic acid building blocks biosynthesis, and the biosynthesis of vancomycin group antibiotics) that could be targeted for therapeutic intervention.